Endocarditis in Mitochondrial Neurogastrointestinal Encephalomyopathy (MNGIE) Syndrome: The First in the Literature - Yolcu, Mustafa (J Clin Diagn Res, 2014)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) syndromes is a rarely seen multisystem disorder with autosomal recessive inheritance due to thymidine phosphorylase gene mutation. It is characterized by progressive external ophthalmoplegia and/or pitosis, progressive gastrointestinal dismotility and abdominal pain, postprandial emesis, cachexia, demyelinating peripheral neuropathy, symmetrical and distal weakness especially in lower extremities and diffuse leucoencephalopathy in cranial magnetic resonance. Endocarditis is the infectious and inflammatory disease of the endothelial surface of the heart. MNGIE syndrome is a condition in which immune system is suppressed and infection risk increased. Herein we summarized a previously not reported endocarditis case in a patient with MNGIE syndrome who was under follow up for three years. In MNGIE syndrome of acute dyspnea, infective endocarditis should be kept in mind and prompt evaluation for surgical treatment should be done.